2021
DOI: 10.1680/jgrim.18.00090
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of cement-treated marine clay under triaxial and plane strain conditions

Abstract: Conventional triaxial compression and unconfined compressive strength tests are the most common testing methods used in the laboratory to determine the shear strength of soil. These tests employ the axisymmetric condition for testing. However, several geotechnical problems in the field can be approximated as plane strain (PS) problems. Hence, testing under PS condition would better represent such field conditions. PS testing has been widely performed on natural soils in the past. However, PS testing on cement-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Figure 4 shows that the of stabilized specimens rises with an increase in gypsum or Portland gel material content, independent of the gel material type. This indicates that cement notably increases the mechanical strength and rigidity of stabilized specimens via the impact of the interlocking and bonding structure [ 28 , 30 , 31 , 34 , 44 ]. Furthermore, unlike the findings reported by Sariosseiri and Muhunthan [ 34 ], all the stabilized specimens in the CU tests showed minimal signs of brittle breakage in their stress–strain curves.…”
Section: Cu Tests Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows that the of stabilized specimens rises with an increase in gypsum or Portland gel material content, independent of the gel material type. This indicates that cement notably increases the mechanical strength and rigidity of stabilized specimens via the impact of the interlocking and bonding structure [ 28 , 30 , 31 , 34 , 44 ]. Furthermore, unlike the findings reported by Sariosseiri and Muhunthan [ 34 ], all the stabilized specimens in the CU tests showed minimal signs of brittle breakage in their stress–strain curves.…”
Section: Cu Tests Results and Discussionmentioning
confidence: 99%
“…Notably, among traditional laboratory methods, consolidation triaxial and UCS tests are prominent for assessing the shear strength of soil or sand. Laboratory experiments have demonstrated that the q ucs of stabilized soil increases as the gel material content rose across various soil types, such as Bangkok soft clay [ 28 , 29 ], marine clays [ 8 , 30 ], and silica sand [ 31 ]. Moreover, multiple researchers have conducted consolidation undrained triaxial (CU) tests to assess the shear strength of cement-treated soils.…”
Section: Introductionmentioning
confidence: 99%
“…In these two test procedures, a cylindrical soil specimen with standard dimensions and a length-to-diameter ratio of 2 is subjected to axisymmetric stress. According to the results of laboratory experiments, the unconfined compressive strength of the treated soil rose with the addition of cement [10][11][12][13][14][15]. The conclusions were based on the test results of different types of soils, including Bangkok soft clay [10,11], marine clays [12,14], Washington State soils [13], and silica sand [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of laboratory experiments, the unconfined compressive strength of the treated soil rose with the addition of cement [10][11][12][13][14][15]. The conclusions were based on the test results of different types of soils, including Bangkok soft clay [10,11], marine clays [12,14], Washington State soils [13], and silica sand [15]. Some researchers have demonstrated that the after-curing void ratio and water-cement ratio are enough to characterize the strength and compressibility of cement-treated clay [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation